Hybrid performance and inbredhybrid relationship of early maturing tropical maize under drought and wellwatered conditions - Oyekunle, M.; Badu-Apraku, Baffour (Springer, 2014)
Drought tolerant maize (Zea mays L.) hybrids are crucial to sustainability of maize production in West and Central Africa (WCA). Two studies were conducted at three locations in Nigeria for 2 yr to (i) assess performance of 156 early-maturing maize inbreds and three hybrid types and (ii) determine heterosis among the lines and relationship between lines per se and hybrid performance. The inbreds and their hybrids were evaluated separately under drought and well-watered conditions. Genotype, environment and genotype × environment interactions were significant for grain yield under the research conditions. Grain yield of inbreds ranged from 0.06 t ha–1 for TZEI 123 to 1.92 t ha–1 for TZEI 17 under drought. While differences in grain yield among hybrid types (single, three-way and double-cross hybrids) were not significant under drought, significant differences were detected among hybrid types under optimal conditions. GGE biplot analysis identified three inbreds, TZEI 18, TZEI 56, and TZEI 1 and hybrids TZEI 129 × TZEI 16, (TZEI 17 × TZEI 16) × TZEI 157 and (TZEI 16 × TZEI 157) × TZEI 129 as ideal across research conditions. Midparent heterosis (MPH) and high-parent heterosis (HPH) for grain yield were higher in the well-watered conditions than under drought. Positive and significant correlations existed between MPH, HPH and yield under both research conditions. Drought tolerant hybrids with stable and high yield are available for promotion for adoption by farmers in WCA.